Application of Artificial Immune System in Structural Health Monitoring. (20th August 2014) - Zhang, Jiachen; Hou, Zhikun
Abstract : A large number of methods have been proposed in the area of structural health monitoring (SHM). However, many of them rely on the prior knowledge of structural-parameter-values or the assumption that the structural-parameter-values do not change without damage. This dependence on specific parameter values limits these methods' applicability. This paper proposes an artificial immune system- (AIS-) based approach for the civil structural health monitoring, which does not require specific parameter values to work. A linear three-floor structure model and a number of single-damage scenarios were used to evaluate the proposed method's performance. The high success rate showed this approach's great potential for the SHM tasks. This approach has merits of less dependence on the structural-parameter-values and low demand on the training conditions.